OPERATIVE MANAGEMENT OF SPORTS TEAMS - GABRIEL IOAN MANGRA; MĂDĂLINA GIORGIANA MANGRA; MARIETA STANCIU (Annals of the University of Petrosani: Economics)
The managerial activities in sport, also known under the name of management in sports or sports management, are similar to those applied by companies, especially in terms of strategic management. However, the operational/operative management is better known for its implementation in sports organizations but the problems raised by this type of management were less addressed when it came to put it in practice within the sports teams. In this paper are presented and analyzed the problems specific for the operative management of professional sports teams in the sport sector and a new typological model of organizations active in sport was elaborated on the basis of these analyzes. There are also presented four styles of operational management applicable to professional sports teams, emphasizing the team-coach relationship and the possible effects of applying these management styles on the teams' performance.